Monitoring the impact of COVID-19 in Myanmar: Agricultural commodity traders - May 2020 survey round - Goeb, Joseph; Boughton, Duncan; Maredia, Mywish K.; Zu, A Myint; Synt, Nang Lun Kham (International Food Policy Research Institute, 2020)
Crop traders comprise the mid-stream of Myanmar’s food supply chain. They form important links between farms and food processors, exporters, and other downstream actors. Because they are close to the farmgate on the supply chain – many purchase agricultural commodities directly from farmers – any additional challenges to traders presented by the COVID-19 crisis and corresponding policy responses have important implications for the crop marketing channels farmers use and for the prices they receive for their crops. Further, challenges or changes to crop trading will have effects on the food system downstream and, ultimately, on consumers. Traders either carry out or facilitate the sales, transport, and purchases of raw agricultural commodities. Thus, they may be negatively affected by the travel and transport restrictions imposed to mitigate the spread of COVID-19 as well as other policy measures that restrict exports or affect food retail channels to consumers. This research note seeks to help the Ministry of Agriculture, Livestock and Irrigation (MOALI) of the Government of Myanmar and agricultural sector stakeholders understand the effects of recent COVID-19 shocks on Myanmar’s agri-food marketing system through the perspective of crop traders. We conducted a phone survey with 154 crop traders to understand the challenges of COVID-19 shocks to both their upstream and downstream operations, (ii) learn about adaptations and changes they are making in response to those challenges, and (iii) track recent (two weeks) and longer-term (last year) changes in the buying and selling prices of the commodities they trade.